Pathogenesis, immune response and laboratory diagnosis of severe acute respiratory syndrome associated Coronavirus 2 - Deepa Revi (Open Journal of Biological Sciences - Peertechz Publications, 2020)
The pandemic unleashed by Severe Acute Respiratory Syndrome Associated Coronavirus 2 (SARS-CoV-2) has crippled the social, health and economic affairs of the world. This is the third stint with a highly contagious virus being introduced into the human population after the Severe Acute Respiratory Syndrome Associated Coronavirus (SARS-CoV) and Middle Eastern Respiratory Syndrome coronavirus (MERS-CoV) incidence in this twenty first century. This mini review provides a brief overview on the basic structure, pathogenesis, immune response and laboratory diagnosis of SARS-CoV-2 for better understanding of the disease process in order to induce novel insights to further intensify the prevention, containment and identification of CoVID-19.